Agriculture, Ecosystems & Environment - Agriculture, Ecosystems & Environment (Elsevier, 2026)
Agriculture, Ecosystems & Environment is a leading interdisciplinary forum that publishes research investigating all aspects of agroecological science. Our objective is to advance understanding of the patterns and processes governing agroecosystem functions, interactions with the environment and provision of ecosystem services. A central theme is how agriculture influences the environment and how changes in that environment impact agroecosystems.
FI 1.72
Q1
Keywords: Life Sciences; Ecosystems; Ecosistemas; Acuerdos transformativos; Transformative agreements; Agroecosistemas; Medio ambiente; Servicios ecosistémicos